6(4j+2+j)=24j+12+6j

Simple and best practice solution for 6(4j+2+j)=24j+12+6j equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(4j+2+j)=24j+12+6j equation:



6(4j+2+j)=24j+12+6j
We move all terms to the left:
6(4j+2+j)-(24j+12+6j)=0
We add all the numbers together, and all the variables
6(5j+2)-(30j+12)=0
We multiply parentheses
30j-(30j+12)+12=0
We get rid of parentheses
30j-30j-12+12=0
We add all the numbers together, and all the variables
=0
j=0/1
j=0

See similar equations:

| 5x-3/4=4 | | 6x-5=6x+48 | | 3x=18+12 | | 13v=159 | | 3^{4x+3}=243^x | | 16x=7.5 | | 7x=2(x-10)=40 | | 5(y-2)+(y-3)=2(2y+1)-9 | | x+986=1.234* | | Z=4+8i | | N+8=8n | | 2x24=10 | | 5(12x+24-26)=250 | | 6/(3x+2)=2/5 | | 122-w=200 | | -x+207=111 | | -6/7u-1/2=-1/3 | | N-16=0.1,n= | | 169=263-u | | 5-3v=32 | | −9x+1=−80x= | | Y=180+50x | | 14=w+19 | | 6-5x=-44# | | /2k+19=1 | | 4.5+(1/120)q=30-(1/60)q | | 2x(x+4)-5=3x-10 | | 5x.2=7 | | 1-1/x=0.95 | | -6d-14=10 | | 3x=6/8 | | 2z+3-1=3z |

Equations solver categories